Regulation and Legal Ethics in the Practice of Dentistry in the Digital Age - Qonitah Nur Aslamiyah; Edi Pranoto (Universitas Muhammadiyah Palu, 2025)
The advancement of digital technology has had a significant impact on various sectors, including dentistry. While technology offers convenience and enhances efficiency in healthcare services, it also brings about challenges related to regulation and legal ethics in dental practice. This article aims to provide a comprehensive review of the regulations governing dental practice in the digital era and the challenges in maintaining ethical and legal standards. The main focus of the discussion includes patient data protection, professional responsibility in the use of technology, the utilization of telemedicine, and the ethical principles that healthcare professionals must uphold. Addressing these challenges requires integrating technological advancements with the implementation of appropriate regulations and a strong awareness of legal ethics to ensure healthcare services remain safe, reliable, and in accordance with legal standards.